The effects of dietary lipids and antioxidants on growth performance, meat quality and moisture loss of the South African abalone, Haliotis Midae - Rousseau, Le-daan Rheeder (Stellenbosch : Stellenbosch University, 2014)
Thesis (MScAgric)--Stellenbosch University, 2014.